Effects of preconditioned plasma collected during the late phase of remote ischaemic preconditioning on ventricular arrhythmias caused by myocardial ischaemia reperfusion in rats - Yang Zhao; Zhi-Nan Zheng; Xiang Liu; Gang Dai; San-Qing Jin (Journal of International Medical Research, 2018)
Objective The administration of preconditioned plasma collected during the late phase of preconditioning has been shown to reduce myocardial infarct size. This study aimed to investigate if preconditioned plasma could attenuate ventricular arrhythmias in a rat model in vivo . Methods Eighty rats were randomized to eight groups (10 rats/group). Two groups provided preconditioned or non-preconditioned plasma 48 h after transient limb ischaemia or the control protocol. Six groups of ischaemia-reperfusion (IR) rats received normal saline, non-preconditioned plasma, or preconditioned plasma, respectively, 1 h (groups A1, A2, A3) or 24 h (groups B1, B2, B3) before undergoing myocardial IR. Electrocardiograms were monitored using a BIOPAC system, and the incidence and duration of ventricular tachycardia (VT) and ventricular fibrillation (VF) were analysed. Results No significant differences existed in the incidence and duration of VT or VF among groups A1–A3 or in the incidence and duration of VT among groups B1–B3. However, there was a significantly lower incidence and shorter duration of VF in group B3 rats than in group B1 rats. Conclusion Preconditioned plasma collected during the late phase of preconditioning can reduce the incidence and duration of VF compared with normal saline, suggesting its anti-arrhythmic potential.